Comparison of Corneal Densitometry and Visual Quality after Small Incision Lenticule Extraction (SMILE) and Laser Epithelial Keratomileusis (LASEK): One-Year Comparative Study. - Cai, Wenting; Liu, Lin; Li, Min; Shi, Yuehui; Sun, Lina; Ma, Xiaoyun; Zou, Jun (BioMed Research International, 2023)
Purpose. To investigate changes in corneal densitometry (CD) and visual quality following small incision lenticule extraction (SMILE) and laser epithelial keratomileusis (LASEK) in patients with mild-to-moderate myopia. Methods. A retrospective analysis was performed on 24 and 25 patients (46 eyes each) who underwent SMILE and LASEK, respectively, for mild-to-moderate myopia. The visual quality and CD values were recorded. Using the Pentacam Scheimpflug system, CD values were collected in three concentric optical zones at the depths of the anterior, central, and posterior layers. Efficacy, safety, predictability, corneal wavefront aberrations, and QoV scores were measured to evaluate visual quality. A correlation analysis was performed between changes in CD and clinical characteristics. Results. There were no statistical differences in efficacy and safety indices between the two groups. At 3 months postoperatively, a pronounced reduction in several zones was observed in the LASEK group (p < 0.05), whereas no obvious change was observed in the SMILE group. There were obvious changes in the CD values in several zones in the SMILE and LASEK groups (p < 0.05) after 1 year. The magnitude of the CD changes in the anterior and central corneal layers was smaller in the SMILE group than in the LASEK group (all p < 0.05). Lower HOAs, spherical aberration, and horizontal comas of the anterior and whole corneal surfaces were observed in the SMILE group. QoV scores were similar between the two groups. Conclusion. CD decreased in the SMILE and LASEK groups after 1 year; there was a smaller reduction in SMILE than in LASEK. SMILE and LASEK did not differ significantly in terms of safety and effectiveness in correcting mild-to-moderate myopia.